Effect of mediator added to modified paste carbon electrodes with immobilized laccase from Aspergillus oryzae - Ferreira, Marcelo Silva; Silva Filho, Arnaldo Fernandes; Martins, Vitor Leite; Andrade, Milena Martins; Giarola, Danilo Antonio; Dall’Antonia, Luiz Henrique (Acta Scientiarum. Technology, 2015)
Carbon paste electrodes based on the immobilization of laccase from Aspergillus oryzae were developed and voltammetric measurements were performed to evaluate the amperometric response. The 2,2â€²-azino-bis-(3-ethylbenzthiazoline-6-sulfonic acid) diammonium saltÂ (ABTS) functions as substrate and mediator for the laccase enzyme. Electrodes were modified Â in two different conditions: without mediator (EPC/laccase) and with mediator (EPC/laccase/ABTS). The addition of ABTS as a mediator increased eight-fold the amperometric response. The electrode was sensitive to pH variation with best response at pH 4.0. Studies on different concentrations of laccase and ABTS at different pH rates revealed that the composition 187 U mL-1 in laccase and 200 ÂµL of ABTS obtained the highest amperometric response. The carbon paste electrode modified with ABTS proved to be a good base for the immobilization of the laccase enzyme. Moreover, it is easy to manufacture and inexpensive to produce a modified electrode with potential application in biosensors. Â Â